Effects of Mesenchymal Stem Cell Secretome on Cardiac Histopathological Changes in Doxorubicin-Induced Rats - Putri, Liza Aulia; Syahrizal, Dedy; Husna, Fauzul; Ridwan, Muhammad; Fitriyani, Sri (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Doxorubicin is an anthracycline chemotherapeutic agent widely used in clinical practice, but its application is limited by cardiotoxicity that damages myocardial structure and function. Mesenchymal stem cell secretome contains diverse bioactive molecules, including cytokines, growth factors, and extracellular vesicles, which contribute to tissue protection and cellular repair. This study aimed to evaluate the preventive and curative effects of secretome administration on histopathological changes in the hearts of doxorubicin-induced rats. Twenty-four rats were divided into four groups: without treatment (KS), cardiotoxicity group (KK), preventive secretome (P1), and curative secretome (P2). Histopathological assessment included degeneration, inflammatory infiltration, congestion, and necrosis using semi-quantitative scoring. Results showed no significant differences in degeneration, inflammatory infiltration, or congestion among groups. In contrast, necrosis scores differed significantly (p = 0.002), with the highest values observed in the KK group. Secretome administration in the P2 group demonstrated the most pronounced improvement, reflected by a greater reduction in necrosis scores compared to other groups. In conclusion, curative-phase secretome treatment provided the most effective histological improvement by reducing myocardial necrosis, indicating a stronger tissue repair response than preventive administration.